FEATURES OF DEVELOPMENT AND USE Computer support in training future lawyers - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article discusses the features of the use of computer support in the training of law students. Analyzesthe didactic function of modern electronic learning tools and opportunities to improve the study ofjurisprudential disciplines in higher education.